Peran Pendidikan Orangtua Dalam Mengatur Pola Asuh Anak - Nasution, Fauziah; Susilo, Dwi Amalia; Lesmana, Nakita Augydia; Anissa, Nur; Assyifa, Salsabila (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This article aims to know and describe the Role of Parental Education in Organizing Childcare. The method used in this research is a literature study to find out about the Role of Parental Education in Organizing Childcare. Parents have a role to help optimize children's growth and development, so that they can achieve their developmental tasks well. The education level of mothers and fathers is an important factor that influences the parenting style of mothers and fathers. This article is written with the aim of conveying information to readers, so that it can be used as a reference to increase readers' knowledge, and can have an academic impact on the author. This article contains about how the Role of Parental Education in Organizing Parenting. Keywords: Parents, Parenting Patterns for Children